Linguistic Typology in Motion Events: Expression of Motion Events in Translated Versions of Turkish and English Novels - Isler, Cemre (Istanbul Univ, Fac Letters, 2022)
This study aims at exploring how speakers of typologically different languages,Turkish verb-framed and English satellite-framed express motion events in translations. In accordance with the aim, the study deals with Turkish and English in terms of statistical and qualitative comparisons in translations and questions how each language adapts itself to the demands of the other in relation to the same content. 6 Turkish and English novels were analyzed for the lexicalization patterns of motion events, and for the diversity of translation strategies adapted by the translators. As for the qualitative comparisons, the translations were further explored in terms of how Turkish translators handle the abundance of verbs with manner information in English texts, and how English translators accommodate Turkish texts to the needs of English. Findings shed light on nuances that should be concerned in the examination of two language types with regard to how each accommodates one another's need for lexicalization patterns and structures. Rather than a strict binary typology, the present study raises an issue that languages can vary within the same typological class, and we cannot take it for granted that languages belong strictly to one group of language. Therefore, along with the findings, discussions of the study highlight the importance of ranging languages in a continuum as eitherhigh-manner-salient language or low-manner salient languagebased on whether they belong to S-or V-type language class.
Keywords: Linguistic typology; motion events; manner of motion verbs,S-languages; V-languages